2017
DOI: 10.1016/j.exger.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The SAMP8 mouse for investigating memory and the role of insulin in the brain

Abstract: SAMP8 mice exhibit changes that commonly occur with normal aging late in life, but do so at a much earlier age. These changes include impairments in learning and memory as early as 8 months of age and so the SAMP8 is a useful model to investigate those age-related brain changes that may affect cognition. As brain insulin signaling and memory decline with aging, the SAMP8 model is useful for investigating these changes and interventions that might prevent the decline. This review will summarize the SAMP8 mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…By the end of 2016, SAMP8 studies appearing in PubMed searches yielded approximately 600 studies. These include the following areas: Alzheimer disease 174; memory deficits 170; dementia 112; Binswanger's disease/vascular dementia 5; Parkinson's disease 5; hydrocephalus 1; oxidative stress 134; amyloid 121; tau 46; neurodegeneration 42; glia 24; therapies 171 (including memory deficits 70 and Alzheimer disease 76); diet 49; neuroprotective effect 26; acupuncture 12; physical exercise 16; and brain insulin 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of 2016, SAMP8 studies appearing in PubMed searches yielded approximately 600 studies. These include the following areas: Alzheimer disease 174; memory deficits 170; dementia 112; Binswanger's disease/vascular dementia 5; Parkinson's disease 5; hydrocephalus 1; oxidative stress 134; amyloid 121; tau 46; neurodegeneration 42; glia 24; therapies 171 (including memory deficits 70 and Alzheimer disease 76); diet 49; neuroprotective effect 26; acupuncture 12; physical exercise 16; and brain insulin 11 …”
Section: Discussionmentioning
confidence: 99%
“…These include the following areas: Alzheimer disease 174; memory deficits 170; dementia 112; Binswanger's disease/vascular dementia 5; Parkinson's disease 5; hydrocephalus 1; oxidative stress 134; amyloid 121; tau 46; neurodegeneration 42; glia 24; therapies 171 (including memory deficits 70 and Alzheimer disease 76); 10 diet 49; 77 neuroprotective effect 26; acupuncture 12; 78 physical exercise 16; 61,62,79 and brain insulin 11. 80 In SAMP strains, SAMP10 mice also have been used as a model for the study of brain aging and age-related neurodegenerative conditions. By the end of 2016, SAMP10 studies appearing in PubMed searches yielded approximately 80 studies.…”
Section: Discussionmentioning
confidence: 99%
“…SAMP8 mice are comparable to normal SAMR1 mice before four months of age, but SAMP8 mice exhibit significant emotional and memory impairments after six months of age; thus, the onset of impairments occurs considerably earlier in SAMP8 mice than in normal SAMR1 mice [ 22 , 23 , 24 , 25 ]. Rhea and Banks (2017) confirmed the appropriateness of SAMP8 mice as an animal model for studies on age-related emotion and memory dysfunction [ 26 ]. They also reported that SAMP8 mice start aging rapidly after four months of age.…”
Section: Introductionmentioning
confidence: 99%
“…We used 16-weeks-old male SAMP8 mice (Japan SLC, Shizuoka, Japan) for in vivo experiments. The SAMP8 mice have spatial learning impairments from 12 weeks of age and spatial memory loss commencing from 16 weeks of age ( Ikegami et al, 1992 ; Flood and Morley, 1997 ; Cheng et al, 2008 ; Rhea and Banks, 2017 ). Also, senescence-accelerated mouse resistant 1 (SAMR1) mice, which have a SAM-related genotype and show resistance to accelerated senescence, were used as controls for SAMP8 as described before ( Takeda, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the senescence-accelerated mouse strain SAMP8 was used as an in vivo model ( Rhea and Banks, 2017 ) to evaluate the effect of sugarcane top extract on pathological aging. This non-transgenic strain shows similar neuropathological features of neurodegenerative diseases such as AD, and encompasses Aβ alterations, increased oxidative stress, augmented tau phosphorylation, as well as learning and memory deficits ( Butterfield and Poon, 2005 ; Pallas et al, 2008 ; Takeda, 2009 ; Morley et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%